197 Combined hyperthermic intraperitoneal chemotherapy and hyperthermic intrathoracic chemotherapy in stage IVA ovarian carcinoma: a tertiary care centre experience. (13th November 2020) - Kumar, N; Ray, MD
Abstract : Introduction: Multidisciplinary team approach with hyperthermic intrathoracic chemotherapy (HITHOC) is a reasonable treatment option for ovarian carcinoma with malignant pleural effusion or pleural deposits. Performing cytoreduction surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC) and HITHOC is a technically demanding procedure. Methods: The data has been collected from a prospectively maintained computerized database. We are sharing our experience of 3 patients with stage IVA ovarian carcinoma patients, which were treated with CRS with HIPEC/HITHOC. Results: Three patients were age 29, 45 and 46 years. All patients were operated after neoadjuvant chemotherapy. Mean cytoreduction surgery and HIPEC/HITHOC time were 370 and 55 minutes respectively. Peritoneal carcinoma indices were 23, 2 and 15 respectively. Cisplatin drug was used in 2 patients with 100 mg dosage at 42°C temperature. Mitomycin (30 mg) was used in one patient. Normal saline was used as perfusate. Completeness of cytoreduction scores of 0 and 1 (CC-0/1) were achieved in 2 and 1 patients respectively. One patient developed Clavien Dindo grade III complication in the post-operative period. All patients received adjuvant Platinum-based chemotherapy because of histological residual disease. All patients are alive until the last visit with a mean follow-up period of 19 months. One patient had recurrent pleural metastasis on follow up. Conclusions: HIPEC/HITHOC is an effective, feasible and safe therapeutic option to prevent recurrence in stage IVA ovarian carcinoma. The postoperative morbidity is acceptable with no recorded mortality. Also, the quality of life improves with HITHOC in the patient having respiratory distress due to malignant pleural effusion/deposits.